Analisis Pendukung Keputusan Dalam Menentukan Pemberian THR Kepada Pensiunan Menggunakan Metode Moora di Kantor Dana Pensiun Perkebunan (Studi Kasus: Dana Pensiun Perkebunan (Dapenbun) - Rahmi, Fadilla Aulia; Sembiring, Boni Oktaviana; Lubis, Ihsan (Universitas Islam Negeri Sumatera Utara, 2022)
The Plantation Pension Fund is a pension fund that manages the defined benefit pension plan (PPMP) for employees of PT. Perkebunan Nusantara, besides that DAPENBUN also provides holiday allowances to retirees in accordance with the regulations set by the company. The purpose of this study is to provide good decisions, provide clear assessments and calculations with criteria that are in accordance with the eligibility to be selected. The method used in this research is the Multi-Objective Optimization On The Basic Ratio (MOORA) method using Hypertext Multi Language (HTML), Hypertext Processor (PHP). In this study, it can be seen that the highest optimization value is (A3) with Yi(max) = (0.381023) with a total THR of Rp. 3,814,406.08 then followed by (A4) which has Yi(max) = 0.303950 with a total THR of Rp. 3,040,792.46 ,(A2) with a value of Yi(Max) = (0.238024) with a total THR of Rp. 2,380,330.24, (A1) with a value of Yi(mx) = (0.227268) with a total THR of Rp. 2,275.423.68 and the smallest (A5) with a value of Yi(Max) = (0.162676) with a total THR of Rp 1,627,251.58. Keywords: holiday allowance, decision support system, MOORA, PHP, HTML, MYSQL.